ANALISIS TATA LETAK FASILITAS PRODUKSI DENGAN METODE FTC DAN ARC UNTUK MENGURANGI BIAYA MATERIAL HANDLING - Casban Casban; Nelfiyanti Nelfiyanti (Jurnal PASTI (Penelitian dan Aplikasi Sistem dan Teknik Industri), 2019)
The progress of the increasingly rapid world of technology has an impact on competition in the increasingly garment industry. Companies that want to be able to continue to survive can even develop to be able to win the competition, they must be able to increase productivity. Steps that can be done by designing the layout of production facilities to be able to reduce the distance of movement of raw material for production. The aim to be achieved in this study is to design the layout of production facilities with the From To Chart (FTC) method and Activity Relationship Chart (ARC) and calculate material handling costs in the production process. The research design used was descriptive exploratory with qualitative and quantitative data approaches to produce an accurate picture of the layout of production facilities and provide a layout design proposal to reduce material handling costs. The calculation results of the material displacement distance of the initial state of 272.6 meters, after improving the layout of the production facilities with the FTC and ARC methods, the distance is reduced to 176.3 meters, so as to reduce the material displacement distance per day by 96.3 meters. Calculation of the initial material handling costs of Rp. 12,267,000, - after repairs were reduced to Rp. 7,933,500, - so as to save material handling costs per day of Rp. 4,333,500, -. Thus it can provide increased profits for the company.